'New Warsaw Pacts', 'Beggar Imperialism' and interstate rivalry in Central and Eastern Europe. (June 2017) - Ilkowski, Filip
This article addresses newly emerging interstate rivalry between Central and Eastern European states based on unevenness of capitalist development and growing assertiveness of particular states in terms of their various strategies and tactics. It critically analyses the efficacy of 'New Warsaw Pacts' concepts and argues that in the Central and Eastern European area, we observe a specific form of a post–Cold War multi-polarity, whereby interstate rivalry is becoming increasingly more complex. The term of 'Beggar Imperialism' is utilized as a possibly useful description of a specific form geopolitical strategy shown by the example of Poland.